2017
DOI: 10.1021/acsami.7b02921
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Metal–Oxide Interactions in Resistive Switching Memories

Abstract: Metal oxides are commonly used as electrolytes for redox-based resistive switching memories. In most cases, non-noble metals are directly deposited as ohmic electrodes. We demonstrate that irrespective of bulk thermodynamics predictions an intermediate oxide film a few nanometers in thickness is always formed at the metal/insulator interface, and this layer significantly contributes to the development of reliable switching characteristics. We have tested metal electrodes and metal oxides mostly used for memris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 47 publications
8
98
0
Order By: Relevance
“…Such kind of observation of device failure with bubble formation is also reported in Hf/HfO 2 /Pt resistive cells. 29 To understand the increase in current with successive voltage pulses with pulse interval of 2 s or less, we analysed the decay of current after every pulse of amplitude 12 V and width 100 ms, Fig. 5(a) Where, I 0 is the steady state current, A is constant and τ is the relaxation time.…”
Section: Resultsmentioning
confidence: 99%
“…Such kind of observation of device failure with bubble formation is also reported in Hf/HfO 2 /Pt resistive cells. 29 To understand the increase in current with successive voltage pulses with pulse interval of 2 s or less, we analysed the decay of current after every pulse of amplitude 12 V and width 100 ms, Fig. 5(a) Where, I 0 is the steady state current, A is constant and τ is the relaxation time.…”
Section: Resultsmentioning
confidence: 99%
“…www.advelectronicmat.de density, [10] (ii) different bond strength [16] of the absorbed moisture to the oxide matrix, and (iii) different interface properties [17,18] (resistance at the electrode/oxide interface or the overpotential for the electrochemical electrode reaction).…”
Section: Resultsmentioning
confidence: 99%
“…The nanobattery effect is often modulated by interface interactions between the electrode and SiO 2 . It has been found that, irrespective of the macroscopic thermodynamic predictions, oxide thin films always form at the interface between active metals and SiO 2 . This oxide film, for example in the case of Cu/SiO 2 , provides an important source of Cu ions.…”
Section: Extrinsic Switching: Electrochemical Reactions and Ecm Resismentioning
confidence: 99%